The Constitutionalisation of the Process - Lorca Navarrete, Antonio María (2016)
This article addresses the relationship between the Process and the Constitution. For this purpose, it is explained what is the object of study of the Procedural Law, and which is the litigation model adopted in article 139 of the Peruvian Constitution, why this model is about a system with its own autonomy and substantivity and not about a subsystem, and how Civil Law and Common Law converging in this model. Furthermore, the author establishes, based on the Constitution, the reason why the existing procedural guarantees in our legal system do not imply a “right to a right decision”, but only the right to a fair process, and explains the difference between “fair process” and “justice” or “judicial truth”.